The Litterateur’s Citadel: fostering literary appreciation in-between the realms of reality-space and fantasy-place - Le Roux, Altus (University of the Free State, 2021)
The term “literature” is often approached as purely educational or academic. However, its origin as stories and tales illuminates a much more significant role of literature. Carried over from generation to generation, literature has the capacity to form a community identity and even an identity of self. Due to this social and cultural significance, literature is undoubtedly worthy of appreciation. The concept of literary appreciation, as well as the role of architecture within this act of appreciation, is investigated. Literature is appreciated when the reader – or writer - is able to experience a part of their own reality within the world of fantasy and fiction in literature. As a result, a place for the appreciation of literature is dependent on both the reality of people and the fantasy of the literary world: a place in-between. In the development of a place for literary appreciation, The Litterateur’s Citadel, the architecture relies on this in-betweenness in order to foster a feeling of appreciation. Due to the similarities between literature and architecture, the Citadel as an in-between realm is predominantly informed by literature itself: the structuring of stories according to The Hero’s Journey is used as a model for literary appreciation through architecture; works of literature are investigated as precedents for the reality-fantasy relationship and the creation of the in-between realm; the act of writing and reading is translated into the notion of creating place. The architecture essentially becomes a piece of literature, a narrative created according to the structure of The Hero’s Journey, a journey through a realm in-between reality and fantasy, a Citadel for the appreciation of Literature.
Dissertation (M.Arch. (Architecture))--University of the Free State, 2021
Keywords: Literature -- Stories, plots, etc.; Storytelling; Literature -- Appreciation; Place for appreciation of literature